MULTIMEDIA FOR DELIVERING PARTICIPANT INFORMED CONSENT IN CARDIOVASCULAR TRIALS. (April 2021) - Chapman, Niamh; Mcwhirter, Rebekah; Armstrong, Matthew; Fonseca, Ricardo; Campbell, Julie; Nelson, Mark; Schultz, Martin; Sharman, James
Abstract : Objective: Obtaining informed consent is a cornerstone requirement of conducting ethical research. Traditional paper-based consent is often excessively lengthy, legalistic in character, and may fail to achieve desired participant understanding of study requirements. Multimedia tools including video and audio may be a useful alternative. This study aimed to determine the efficacy, usability and acceptability of stand-alone multimedia delivery of participant consent relating to a cardiovascular trial. Design and method: A total of 298 participants (63 ± 8 years; 51% female) were randomised to delivery of cardiovascular research study information and signed consent via multimedia (intervention; n = 146) compared with standard paper-based approach (control; n = 152) in a clinical research setting. Intervention was free of research staff and included short audio-visual explanations, with computer-based finger-signed consent. Efficacy, usability and acceptability were assessed by questionnaire. Results: All participants successfully completed allocated interventions. Efficacy parameters were significantly higher among intervention participants, including better understanding of study requirements compared with controls (P < 0.05 all). Intervention participants were also significantly more likely to engage with the study information and spend more time on the consent process and study questionnaire (P = 0.038 and P = 0.007, respectively). Both groups reported similar levels of acceptability of the consent process, although more control participants reported that the study information was too long (24% versus 14%; P = 0.020). Conclusions: A standalone multimedia consent process is effective for achieving participant understanding and obtaining consent on cardiovascular research in a clinical research setting free of research staff. Thus, multimedia represents a viable method to reduce the burden on researchers, meet participant needs, and achieve informed consent in clinical cardiovascular research.